Identifikasi Grade Sapi Bali Betina Bibit dan Koefisien Reproduksi Sapi Betina di Propinsi Nusa Tenggara Barat (Grade Identification and Reproductive Coefficient of Bali Cattle Breeding Female in West Nusa Tenggara Province) - Soekardono (Soekardono); Chairussyhur Arman; Lalu Muhammad Kasip (Buletin Peternakan, 2009)
The goals of the research were to determine grade of Bali cattle breeding female and coefficient of reproduction of cattle breeding farm in NTB. Research was conducted in West Lombok Regency representing Lombok Island and Dompu Regency representing Sumbawa Island. Determination of cattle grade was carried out by measuring body weight, body length, shoulder height, and girth circle, as well as exterior observation, followed by data analysis with statistical descriptive tool. In order to know coefficient of reproduction, interviewed were implemented to the farmers (respondents), and then data were analyzed descriptively with the aid of table. Results of the study indicated that with the criteria of Directorate General of Livestock Services (DGLS) 2006, based on shoulder height (HS), grade of Bali cattle breeding female in NTB could be classified into: grade I = 36.5%; II = 49%; III = 7.5%; and non grade (NG) = 7%; based on body length (BL): grade I = 38.5%; II = 46%; III = 7.5%; and NG = 8%. When  classification was considered based on island region, it showed that grade of Bali cattle breeding female in Sumbawa was better than that of in Lombok islands. Grade of Bali cattle breeding female in Lombok Island, based on HS was found as the following: grade I = 19.8%; II = 62%; III = 11%; and NG = 7%; while based on BL: grade I = 18.8%; II = 61%; III = 10%; and NG = 9%. Grade of Bali cattle breeding female in Sumbawa Island, based on HS was as the following: grade I = 57%; II = 34%; III = 3%; and NG = 7%; while based on BL: grade I = 61%; II = 29%; III = 4%; and NG = 6%. From technical coefficient of reproduction view point, the calving interval and weaning calf age were still quite long, about 15 and 6 months, respectively.(Key words: Grade of Bali cattle breeding, Coefficient of reproduction, Bali cattle breeding female)